The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.32479/ijeep.14134
|View full text |Cite
|
Sign up to set email alerts
|

Gas Consumption as a Key for Low Carbon State and its Impact on Economic Growth in Malaysia: ARDL Approach

Abstract: Natural gas consumption contributes the least to CO2 emissions than other non-renewable energy such as oil and coal. Thus, it is important to replace oil in generating economic activities and leading the country towards low carbon state. Despite the environmentally friendly energy, most previous studies did not study gas consumption. Therefore, this study investigates the effects of gas consumption and other selected macroeconomic determinants such as labour, capital, foreign direct investment, trade openness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A comprehensive review of this literature is essential to grasp previous findings and identify existing research gaps. Many of these studies have demonstrated that finite energy sources and economic prosperity worsen environmental degradation, while renewable energy helps to mitigate it [ 9 , [28] , [29] , [30] , [31] , [32] ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive review of this literature is essential to grasp previous findings and identify existing research gaps. Many of these studies have demonstrated that finite energy sources and economic prosperity worsen environmental degradation, while renewable energy helps to mitigate it [ 9 , [28] , [29] , [30] , [31] , [32] ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Khan et al [ 51 ] observed that exports and renewable energy consumption are associated with decreased carbon energy, while imports and GDP show an increasing trend. Focusing on the D8 countries, Majekodunmi et al [ 9 ] shed light on the negative association between exports, population growth, and environmental deterioration in the D8 countries. While exports and population growth generally increased environmental deterioration, the authors identified a mitigating effect of exports on emissions in Malaysia, Pakistan, and Turkey, particularly in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, green energy is a cutting-edge and environmentally friendly choice for reliable power, Majekodunmi et al (2023). In addition to being crucial for the planet, the consistent and low-cost advantages of renewable energy can improve social and fiscal prospects in developing nations (Rahman et al, 2022;Ergun et al, 2019;Akizu-Gardoki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) emissions, predominantly from human activities, have become a significant concern due to their detrimental impact on the environment (Shaari et al, 2022a;Shaari et al, 2022b;Shaari et al, 2023;Ridzuan et al, 2018;Rennert et al, 2022;Voumik et al, 2023;Mohamed Yusoff et al 2023). The excessive release of CO 2 into the Earth's atmosphere is primarily responsible for global warming and climate change.…”
Section: Introductionmentioning
confidence: 99%